The turnaround from transgression to regression of Holocene barrier systems in south‐eastern Australia: Geomorphology, geological framework and geochronology. Issue 3 (27th December 2020) - McBride, Randolph A.; Oliver, Thomas S. N.; Dougherty, Amy J.; Tamura, Toru; Carvalho, Rafael C.; Short, Andrew D.; Woodroffe, Colin D.
Abstract: Holocene regressive strandplains that preserve a series of former shorelines are extensive on coasts that were remote from major Pleistocene ice sheets (for example, Australia and Brazil), whereas transgressive barrier islands are typical in glacial forebulge regions (for example, North America and Europe). In strandplains, the regressive phase of strandline development was preceded by a transgressive phase during the final stages of postglacial sea‐level rise. This study examines the turnaround from transgression to regression through chronostratigraphic description of three barrier systems in south‐eastern Australia: Seven Mile Beach, Bengello Beach and Pedro Beach. The authors reconstruct geomorphic and depositional histories using ground‐penetrating radar and vibracores along transects across the landwardmost ridges, and optically‐stimulated luminescence and radiocarbon dating. At the Seven Mile Beach barrier system, extensive washover deposits are preserved that include distinctive, landward‐directed, flame‐shaped washover fans along the bayside shoreline of the landwardmost ridge. Landward‐dipping ground‐penetrating radar reflections in radargrams provide evidence of the culmination of the transgressive phase and transition into the regressive phase dominated by progradation, evidenced by the change to seaward‐dipping reflections. A similar progradational plain formed at the Bengello Beach barrier system, but transgressive deposits are largely absent at the site investigated, where an eroded headland created limited accommodation space until sand supply was sufficient for progradation. The Pedro Beach barrier system depositional history is more complex. There, a smaller embayment filled rapidly during the mid‐Holocene, and transgressive sands were deposited as sea level reached its present level and impounded a wetland. Accommodation space in the embayment was filled by ca 4000 years ago. Overall, results indicate that the Holocene turnaround transition occurred between 8400 and 7000 years ago, and was preserved at the landward margin of these three strandplains. Holocene morphostratigraphy differs among sites primarily as a function of sea level, sediment supply and antecedent topography.